KEPASTIAN HUKUM KETENTUAN WAJIB MUNDUR TENAGA PENDAMPING PROFESIONAL (TPP) SEBAGAI CALON ANGGOTA LEGISLATIF - Munandar, Agung; Zulfikar, Muhammad Nahyan; Muharrir, Muharrir; Adabi, Muhammad Ikhwan (Prodi Ilmu Hukum, Universitas Teuku Umar, 2025)
A situation involving Professional Assistance Personnel (TPP) running for legislative office has emerged in Langkat District. Two legislative candidates from the National Awakening Party (PKB) are also registered Village TPPs. Concurrently, Komnas HAM received a complaint alleging that the Ministry of Villages (MoV) terminated the employment of 1,040 TPPs because they became legislative candidates. However, the TPP employment contracts reportedly lack clauses prohibiting political candidacy, raising legal questions regarding the employment status of TPPs. This study aims to determine the regulations concerning the resignation requirements for TPPs seeking legislative office, in accordance with applicable legislation. Employing a socio-legal approach, the research finds that TPPs are eligible to run as legislative candidates provided they meet the necessary requirements. Nevertheless, TPPs must resign from their positions because funding for TPP roles originates from the state budget. TPPs are considered Ministry personnel, and those committing serious violations, such as serving in political party management, face sanctions including dismissal.